China's Belt and Road (BRI) Policy for Trade Interests in Indonesia - Riska, Riska Fatmala Dewi (Jurnal Suara Hukum, 2024)
In promoting international trade within Indonesia, the government relies on Law Number 7 of 2014 concerning Trade. This legislation serves as a foundational framework for facilitating trade activities and addressing related issues. As part of efforts to bolster infrastructure development amidst financial constraints, Indonesia has turned to initiatives such as the Chinese Silk Road, or Belt and Road Initiative (BRI). This strategic partnership aims to enhance Indonesia's infrastructure capabilities, particularly in light of budgetary limitations that have hindered optimal development. However, the implementation of BRI projects has sparked concerns and varying interpretations, particularly regarding the potential risks of falling into a "debt trap" or succumbing to "debt diplomacy" with China. This research employs a normative juridical approach, utilizing statutory analysis and conceptual frameworks to explore these complexities. A notable case is the Jakarta-Bandung high-speed rail project, slated for operation by August 18, 2023, which exemplifies BRI's application in Indonesia. Addressing legal uncertainties and ensuring robust dispute resolution mechanisms are crucial for mitigating risks associated with BRI policies. It is imperative for Indonesia to proactively safeguard against adverse impacts while harnessing the benefits of international partnerships for sustainable development.